2020
DOI: 10.21203/rs.2.18586/v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An immunoinformatic approach driven by experimental proteomics: in silico design of a subunit candidate vaccine targeting secretory proteins of Leishmania donovani amastigotes

Abstract: Background Visceral leishmaniasis (VL) caused by dimorphic Leishmania species is a parasitic disease with high socioeconomic burden in endemic areas worldwide. Sustaining control of VL in terms of proper and prevailing immunity development is a global necessity amid unavailability of a prophylactic vaccine. Screening of experimental proteome of the human disease propagating form of Leishmania donovani (amastigote) can be more pragmatic for in silico mining of novel vaccine candidates. Methods By using an immun… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Previous studies have shown that the immunogenicity of amastin sequences are furthermost than all surface antigens of Leishmania in mice (Stober et al, 2006) and show intense immunogenicity with human visceral leishmaniasis (Rafati et al, 2006). A low molecular weight protein may be an efficient target for vaccine candidacy (Khan et al, 2020). Diverse amastin protein are translated in L. donovani amastigotes in individuals with visceral leishmaniasis (Rochette et al, 2005; de Paiva et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the immunogenicity of amastin sequences are furthermost than all surface antigens of Leishmania in mice (Stober et al, 2006) and show intense immunogenicity with human visceral leishmaniasis (Rafati et al, 2006). A low molecular weight protein may be an efficient target for vaccine candidacy (Khan et al, 2020). Diverse amastin protein are translated in L. donovani amastigotes in individuals with visceral leishmaniasis (Rochette et al, 2005; de Paiva et al, 2015).…”
Section: Introductionmentioning
confidence: 99%